Oral Granular Cell Tumor: Report of Case Series and a Brief Review of the Literature - Karakostas Panayiotis; Matiakis Apostolos; Anagnostou Eleftherios; Kolokotronis Alexandros (Balkan Stomatological Society, 2017)
Background/Aim: The present analysis focuses on examining a case series of eight patients diagnosed with a granular cell tumor located in the oral cavity. Case series: The patients' clinical states were thoroughly studied, along with the histopathological and immunohistochemical examinations findings. Their surgical treatment and postoperative course are also within the scope of this analysis. Numerous histogenesis theories and the appropriate tumor treatment are mentioned within the article being always in accordance with the relative literature. Conclusions: Oral granular cell tumor is a benign oral disease of possible neural origin commonly located on the tongue. Surgical excision is the treatment of choice. In any case, histological and immunohistochemical examination confirm both the clinical diagnosis and the differential diagnosis between oral squamous cell carcinoma.